Types of Problematics that Affect Undergraduates' Competence in Translating English Collocations and Phrasal Verbs - Fahima Mohamed Bannur; Dalya Abdullah Akkila; Fawzia Mohamed Elwafi (FOSTER: Journal of English Language Teaching, 2022)
This study explores the Libyan undergraduates' capability to comprehend English collocations and phrasal verbs and translate them into Arabic. It also targets investigating the types of obstacles that these students encounter when they translate English collocational expressions. The methodology used in this study was based on quantitative and qualitative methods where a translation test consisting of two main parts was given to sixty-two (62) female undergraduates from the English department, Faculty of Education, University of Tripoli. An in-depth analysis of participants' answers was performed, and the results were reported. The study concluded that the participants struggled to translate English collocations and phrasal verbs. In addition, the translation production reveals that grammatical, lexical, and cultural problems were the main problem areas identified in students' answers. These problems are related to the influence of LI (Arabic), lack of appropriate vocabulary, difficulty in understanding vocabulary use, lack of translation practice, the misuse of literal translation and translation teaching methods. However, though the cultural gap between L1 (Arabic) and L2 (English) is huge, it could be minimized and bridged by using new techniques in teaching collocations and translation and frequent practice in translation.